Effect of Organizational Commitment, Compensation and Job Satisfaction on Employee Performance Through Organizational Citizenship Behavior In Bank BPD DIY Employees Senopati Branch Office - Seran, Godeliva Leni; Subiyanto, Didik; Kurniawan, I.Soni (Bina Bangsa International Journal of Business and Management, 2021)
This study aims to determine the factors that affect the performance at the BANK BPD DIY Senopati branch office. The method in this research is accidental sampling. The analytical method used is the classical assumption test, t-test and Sobel test. Based on the research results, it is known that commitment has a significant positive effect on OCB, compensation has a significant effect on OCB, and satisfaction does not affect OCB, while commitment has a significant effect on employee performance, compensation has a significant positive effect on performance, job satisfaction has no effect on performance. OCB has a positive effect on employee performance. commitment has a significant positive effect on performance with the OCB variable as an intervening variable, compensation has a significant effect on performance with OCB as an internal variable has no significant effect on performance through OCB As an intervening variable and job satisfaction It is expected that this research can be used to measure commitment, compensation, and employee satisfaction as well as OCB on employee performance behavior